Molecular characterization and expression profile of estrogen receptor subtypes in female hilsa (Tenualosa ilisha) - Roy, Arpita; Kumar, Vikash; Bisai, Kampan; Bhowal, Pratyasha; Panda, Soumya Prasad; Jana, Asim Kumar; Banerjee, Rajat; Das, Basanta Kumar (Frontiers in Marine Science, 2024)
Hilsa (Tenualosa ilisha), a highly prized edible fish, is consumed by over 250 million people worldwide. Estrogens are essential hormones required during reproduction and bind with estrogen receptors in target organs for biological activity. The two unique subtypes of the estrogen receptor found in fish are alpha (α) and beta (β) and exhibit distinctive roles in reproduction. The present study aimed to understand the breeding physiology of hilsa during the seasonal gonadal cycles through GSI seasonal variation, histological study and molecular identification, characterization, and transcriptional modification of estrogen receptors in Hilsa.Monthly GSI analysis from females showed that during September, the GSI value was maximum (22.01 ± 0.68), followed by the May GSI value (18.78 ± 0.97). Histological observation showed the formation of asynchronous gametes during the development of ovaries. The histological analysis revealed the formation of developing oocytes, nucleus, presence of primary oogonia, secondary oogonia, chromatin nucleolar oocytes and early perinucleolar oocytes in the ovary (January -early July). Progressively, formations of the yolk vesicles, yolk granule stage, pre-mature stage, and mature stage with post-ovulatory follicles were also identified. Liner observation was recorded during the monsoon season from July to November. Furthermore, partial length cDNAs for estrogen receptors were characterized, and their mRNA expression patterns demonstrate that ER-α expression significantly increased in September, followed by April and August in the ovary and liver tissue. Both the liver and ovary showed the highest mRNA expression of ER-β in September. The study revealed that ER-α expression was higher in the ovary as compared to liver tissue. Furthermore, we introduce three-dimensional (3D) models depicting the hilsa estrogen receptors in complex with estradiol (E2), constructed through homology modeling. This investigation contributes valuable insights into the molecular characteristics of estrogen receptors in this teleost fish.Our present work provided preliminary evidence of estrogen receptors during reproduction in Hilsa.